Implementation of Simple Additive Weighting in Providing Micro Business Loans at Bank Mandiri Pematangsiantar - Sahat Sonang Sitanggang; Erwin Sirait (Information Technology and Science (ITScience), 2021)
Banks are institutions and institutions that are organizations and institutions in Indonesia and have an important role in the sustainability of the Indonesian economy. Bank Mandiri is one of the banks that provides micro business credit facilities to the business world. The higher the public's interest in getting micro business credit, the banks need software to help determine who is entitled to credit. In order to produce a proper feasibility analysis, a method of decision-making in overcoming these problems is needed so that determining who is entitled to receive credit is not too long and efficient in reducing credit risk. Problems arise in the decision-making process for granting micro-business loans, namely the inaccuracy of micro-business credit recipients. The above problems can be resolved by building a Decision Support System which can assist decision makers in assessing and selecting micro business loans using variables: Income, Collateral, Loan Limit, Installments, Length of Business, Number of Dependents. The system built by applying the Simple Additive Weighting method is known as the method of adding weight. The Simple Additive Weighting method requires a decision matrix normalization process to a scale that can be compared with all available alternative ratings. This will be a reference in ranking and consider the advantages and disadvantages of applying for a credit loan in order to find the desired candidate. From the test results using 10 data samples, it was obtained that the first rank was received credit on behalf of A5 with a value of 9.33, and the last rank was on behalf of A6 with a value of 6.4. and very helpful in solving problems faced by Bank Mandiri Pematangsiantar.